2023
DOI: 10.3390/bs13080692
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Appearance Anxiety on Social Anxiety among College Students: Sequential Mediating Effects of Self-Efficacy and Self-Esteem

Jieying Liao,
Tiansheng Xia,
Xuan Xu
et al.

Abstract: Social anxiety is a serious psychological problem prevalent among Chinese college students, and appearance anxiety plays an important role in its development. Although some studies have explored the relationship between the two, the mediating mechanism is unclear. This study constructed a sequential mediation model based on the cognitive–behavioral theory of body image disorder and social phobia to explore the mediating role of self-efficacy and self-esteem. A total of 234 college students were recruited using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…In this study, it was determined that there was a positive relationship between Social Appearance Anxiety and Self-Esteem. Liao et al 29 As a result of the study conducted, it was determined that there was a positive relationship between social appearance anxiety and self-esteem. However, Göbel et al In the study conducted, it was determined that there was a negative relationship between social appearance anxiety and self-esteem.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was determined that there was a positive relationship between Social Appearance Anxiety and Self-Esteem. Liao et al 29 As a result of the study conducted, it was determined that there was a positive relationship between social appearance anxiety and self-esteem. However, Göbel et al In the study conducted, it was determined that there was a negative relationship between social appearance anxiety and self-esteem.…”
Section: Discussionmentioning
confidence: 99%
“…Appearance influences the formation and establishment of self-esteem in adolescence and young adulthood. External anxiety can lead to a lack of confidence and negativity and further a decrease in an individual’s level of self-esteem, resulting in an inability to integrate into society and positively face the challenges of interpersonal relationships ( Liao et al, 2023 ). Hairi et al found that a person’s dissatisfaction with his or her appearance can lead to lowered self-esteem, which in turn can trigger depression ( Hai & Yang, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, excessive anxiety that interferes with daily functioning can have a detrimental impact on overall wellbeing. (8,9) Anxiety is a common mental health disorder found frequently in Indonesia and worldwide. The World Mental Health Surveys in 21 countries estimated that 9.8% people were affected by anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%